Short communicationDedicated devices and techniques – a cornerstone in recanalisation of chronic total occlusions of coronary arteries - Bryniarski, Leszek; Kusak, Piotr; Surowiec, Sławomir; Dudek, Dariusz; Czarnecka, Danuta (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Recanalisation of chronic total occlusion (CTO) is still a challenge in invasive cardiology, requiring operator experience, equipment, and techniques dedicated to CTO. Due to difficulties in crossing the lesion by wire and by balloon (both responsible for 98% of the procedure’s failures), many helpful techniques have been described. We report the case of both Tornus system and anchor technique in successful recanalisation of a right coronary artery.